2010
DOI: 10.1136/jnis.2010.003251.4
|View full text |Cite
|
Sign up to set email alerts
|

E-004 Cranial dural arteriovenous fistulas: asymptomatic cortical venous drainage portends less aggressive clinical course

Abstract: ObjectiveCranial dural arteriovenous fistulas (dAVFs) with cortical venous drainage (CVD) (Borden type 2 and 3) are reported to carry a 15% annual risk of intracranial hemorrhage (ICH) or non-hemorrhagic neurological deficit (NHND). The purpose of this study is to compare the clinical course of type 2 and 3 dAVFs that present with ICH or NHND versus those that do not.Methods28 patients with type 2 or 3 dAVFs were retrospectively evaluated. CVD was classified as asymptomatic (aCVD) if patients presented inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 0 publications
2
95
0
Order By: Relevance
“…It has been reported that patients presenting with benign (incidental/pulsatile tinnitus/orbital phenomena) symptoms from cDAVFs with CVD may be at lower annual risk for intracranial hemorrhage (approximately 1.5%) compared with those presenting with aggressive neurologic symptoms. [14][15][16] However, these estimates are based on small patient numbers or short follow-up periods. In the series by Strom et al, 15 1 of 17 patients presenting with benign symptoms from persistent CVD bled 13 years later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients presenting with benign (incidental/pulsatile tinnitus/orbital phenomena) symptoms from cDAVFs with CVD may be at lower annual risk for intracranial hemorrhage (approximately 1.5%) compared with those presenting with aggressive neurologic symptoms. [14][15][16] However, these estimates are based on small patient numbers or short follow-up periods. In the series by Strom et al, 15 1 of 17 patients presenting with benign symptoms from persistent CVD bled 13 years later.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] However, these estimates are based on small patient numbers or short follow-up periods. In the series by Strom et al, 15 1 of 17 patients presenting with benign symptoms from persistent CVD bled 13 years later. In another series by Söderman et al, 14 a complicated "time-at-risk" period was calculated by combining the time between symptom onset/nonangiographic diagnosis, the time between diagnostic angiography and treatment, and clinical follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Strom et al reported a similar annual hemorrhage rate of 1.4% in 17 patients harboring DAVFs with CVD without prior hemorrhage. 45 The risk increased to 7.6% in those with DAVFs with CVD who presented with hemorrhage or nonhemorrhagic neurological deficit. Detailed analyses by Gross and Du of published studies found 6% and 10% annual hemorrhage rates for Borden Types II and III DAVFs, respectively, in contrast to an annual hemorrhage rate of 0% for Borden Type I DAVFs.…”
Section: Comparison Of Davfs With Cvd and Davfs Without Cvdmentioning
confidence: 99%
“…12, 63,70 Morbidity correlates more with the severity of DAVF retrograde cortical venous reflux as classified by the Borden and Cognard grading systems, and not necessarily the location of the DAVF. 4,10,15,24,34 In patients with DAVFs with cortical venous reflux, the annual rate of intracranial hemorrhage or nonhemorrhagic neuro logical deficit is 15-19%.…”
Section: Dural Arteriovenous Fistulasmentioning
confidence: 99%
“…4,10,15,24,34 In patients with DAVFs with cortical venous reflux, the annual rate of intracranial hemorrhage or nonhemorrhagic neuro logical deficit is 15-19%. 63,70 Dural arteriovenous fistulas without cortical venous reflux, have a low risk of hemor rhage 14,19 and have been reported to undergo spontaneous regression. 38 In 1972, Houser et al 24 observed the development of DAVFs in patients with previous venous thrombosis docu mented by catheter angiography.…”
Section: Dural Arteriovenous Fistulasmentioning
confidence: 99%